2007
DOI: 10.1007/s12264-007-0053-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heartbeat perception on heartbeat evoked potential waves

Abstract: Objective Early researches found that different heartbeat perceivers have different heartbeat evoked potential (HEP) waves. Two tasks were considered in our experiments to get more details about the differences between good and poor heartbeat perceivers at attention and resting state. Methods Thirty channels of electroencephalogram (EEG) were recorded in 22 subjects, who had been subdivided into good and poor heartbeat perceivers by mental tracking task. Principal component analysis (PCA) was applied to remove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 14 publications
8
36
1
Order By: Relevance
“…Previous studies have demonstrated a positive association between heartbeat perception accuracy in the Schandry task and HEPs when assessed during this task, but not when assessed during rest (22,79). In the current study, the correlation between HEPs and accuracy in the Schandry task was low and not significant (r = 0.151, p = .33), which may be due to the fact that HEPs in the current analysis were aggregated over the Schandry task and the resting period.…”
Section: Discussioncontrasting
confidence: 74%
“…Previous studies have demonstrated a positive association between heartbeat perception accuracy in the Schandry task and HEPs when assessed during this task, but not when assessed during rest (22,79). In the current study, the correlation between HEPs and accuracy in the Schandry task was low and not significant (r = 0.151, p = .33), which may be due to the fact that HEPs in the current analysis were aggregated over the Schandry task and the resting period.…”
Section: Discussioncontrasting
confidence: 74%
“…Up to 450 ms after the R wave, the HEP amplitude and the electrocardiac field partially overlap (Dirlich, Vogl, Plaschke, & Strian, ; Schandry et al., ). In the literature, there were different approaches described to overcome this possible confounding factor: in some studies, the electrocardiac field was eliminated using the Hjorth source derivation method (Pollatos et al., ; Pollatos & Schandry, ), others subtracted components possibly originating from the ECG via principal (Yuan, Yan, Xu, Han, & Yan, ) or independent component analysis (Terhaar, Viola, Bar, & Debener, ), and some newer studies limited the analysis on a time window of 455–595 ms after the R wave, during which the electrocardiac field is considered minimal (Gray et al., ; Schulz, Strelzyk et al., ). Here, we used the latter approach and analyzed HEP amplitudes during the previously established interval of R +455–595 ms. HEP amplitudes of F3 and F7, as well as F4 and F8, were collapsed to create an equal‐sized 3 (frontal, central, parietal) × 3 (left, midline, right) electrode field on the scalp.…”
Section: Methodsmentioning
confidence: 99%
“…Kuehn and co-workers [51] found only right-hemispheric activation in participants with high cardioceptive accuracy. Further evidence for right-insular dominance for interoception comes from electroencephalography-(EEG-) based dipole source-localization studies [97,98]. EEG studies on the so-called heartbeat-evoked potential also have shown greater amplitudes over right electrode positions for subjects with high cardioceptive accuracy/ sensitivity [99,100].…”
Section: (B) On Hemispheric Specializationmentioning
confidence: 99%